Pengaruh Model Reciprocal Teaching terhadap Pemahaman Konsep Matematis Siswa Ditinjau dari Self-Efficacy - ROHMAYANI, PUTRI; Candra Hastari, Ratri (Progressive of Cognitive and Ability, 2022)
The purpose of this study is to analyze: (1)the effect of appliying the reciprocal teaching learning model on students’ mathematical concept understanding ability; (2)differences in the ability to understand mathematical concepts in terms of student self-efficacy; (3)interactions between reciprocal teaching learning models, ability to understand mathematical concept and self-efficacy. This type of research is pseudo-experimental research with a quantitative approach. The population used in this study was all classes VIII at SMPN 4 Tulungagung and the sampels used were classes VIII-G and VIII-H with a total of 61 students. The data collection tecniques used are test and questionaries. The data analysis used includes equilibrium test, normality test, homogeneity test, hypothesis test and comparation test. Based on the results of the study, it can be concluded that: (1)there is an influence of reciprocal teaching learning model on the ability to understand mathematical concept where, F-count greater than the F-table (7,73>4,06); (2)there are differences in the ability to understand mathematical concepts in terms of student self-efficacy where, F-count greater than F-tabel (20,35>3,21); (3)there is no interaction between the reciprocal teaching learning model, the ability to understand mathematical concepts and the self-efficacy of students where, F-count smaller than F-table (0,605<3,21)